Analysis Of Factors Affecting Money Demand In Indonesia Year 2006-2015 With Approach Error Corection Model (ECM) - Muhammad Nur; Sinta Yulyanti; Nuriman M. Nur (Jurnal Ekonomi KIAT, 2017)
This study is a study of the demand for currency in Indonesia in the period 2006-2015. The focus of this research is to analyze what factors affect the demand for currency in Indonesia in 2006-2015. Inflation in the short and long term has a positive and significant relationship to the demand for money in Indonesia. Short-term interest rates have a negative and insignificant relationship while in the long run have a negative and significant relationship to the demand for money in Indonesia. Gross Domestic Product (GDP) in the short term has a positive and insignificant relationship to the demand for money in Indonesia while in the long run the GDP has a positive and significant impact on the demand for money in Indonesia.